Portosystemic Encephalopathy in a Noncirrhotic Patient Treated by Vascular Plug Embolization of Mesoiliac Shunt - Othman Alshehre; Faisal Alahmari; Sultan Alammari; Abdulaziz Almathami; Hatim Alobaidi; Ibrahim Alrashidi; Marwan Alosaimi; Fares Garad (The Arab Journal of Interventional Radiology, 2020)
Mesoiliac shunts in the absence of liver cirrhosis are rarely reported as a cause of hyperammonemia with encephalopathy. Here, we report the case of a 65-year-old female patient with no history of liver disease, who developed significant confusion. Workup showed hyperammonemia and encephalopathy due to spontaneous mesoiliac shunt with no imaging signs of portal hypertension. Liver biopsy showed no evidence of cirrhosis. The shunt was occluded using a vascular plug, resulting in complete resolution of symptoms with no recurrence at 8-year follow-up.